Hubungan Kelainan Refraksi, Durasi Melihat Layar dan Durasi Istirahat dengan Kejadian Computer Vision Syndrome pada Pekerja Operator Minegem PT. F - Armaniel Ababil; J. Mukono (Media Gizi Kesmas, 2023)
Background: PT. F is an underground mining company that has a high level of risk in its work. With these conditions, PT. F uses a mining material retrieval system with remote LHD (load, haul, dump) truck control using a minegem system. Minegem operator workers have a work system of 1 shift of 12 hours per day with work support in the form of monitors (>2 monitors for each operator) and also control minegems using joysticks. This condition increases the risk of the occurrence of computer vision syndrome in minegem operator workers. Objectives: This study aims to find risk factors associated with the incidence of computer vision syndrome in minegem operator workers PT. F in 2023. Methods: The research method used was observational analytical research with a cross-sectional approach. Data collection methods included observation and filling out validated questionnaires. The Slovin formula was used to calculate samples using the random sampling technique Results: The study's findings indicated that the variable refractive error (p-value =0,027) and length of time between computer uses (p-value =0,041) had a significant link with the incidence of computer vision syndrome Conclusion: The study's findings indicated that refractive abnormalities and the amount of time spent away from the computer had a significant impact on the incidence of computer vision syndrome in minegem operator workers in 2023. As a result, it was recommended that the company provide ergonomic information to minegem operator workers and implement 20-20-20 movements to reduce the risk of developing computer vision syndrome in PT. F minegem operator workers.